THU0454 Changes in DNA Methylation Related to Smoking Are Associated with Ra. an Epigenome Wide Association Study in Monozygotic RA Discordant Twin Pairs. (10th June 2014) - Svendsen, A.J.; Gervin, K.; Lyle, R.; Nielsen, C.; Houen, G.; Junker, P.; Kyvik, K.; Tan, Q.
Abstract : Background: There is increasing evidence for a pathogenetic role of DNA methylation changes in RA. Monozygotic (MZ) twins provide a unique opportunity to study the epigenetic effects in complex diseases like RA. Recent estimates on DNA methylation in twins showed a mean genome-wide heritability of 18%. Recent studies indicate that DNA methylation may be an intermediary factor of genetic risk in RA. 1 In addition, tobacco smoking, which has emerged as the single most important environmental risk factor for RA, leads to extensive Genome-Wide changes in DNA methylation. 2 Objectives: To identify differentially methylated positions (DMPs) associated with RA and smoking. Methods: Blood-derived DNA from 28 monozygotic RA discordant twin pairs was analyzed for epigenome wide methylation (EWAS) using Illumina HumanMethylation450 array. The twins were characterized with regard to smoking, DMARD-treatment, anti-CCP, and the pair specific genetic variables shared epitope and PTPN22 as well as age and sex. We used a mixed model designed for EWAS on discordant twins taking these covariates as well as batch effects into consideration. Results: A total of 407 CpG sites were differentially methylated in RA patients related to smoking with p<0.01, adjusted for false discovery rates. Biological pathway analysis revealed that a large number of functional gene clusters were affected, e.g. macrophage activation, sphingomyelin metabolic process, apoptotic cell clearance, and histone demethylase activity. Conclusions: These observations indicate that tobacco smoking elicits profound epigenetic modifications in RA when adjusting other RA associated covariates. References: Liu Y, Aryee MJ, Padyukov L, Fallin MD, Hesselberg E, Runarsson A, et al. Epigenome-wide association data implicate DNA methylation as an intermediary of genetic risk in rheumatoid arthritis. Nat Biotech 2013; 31(2): 142-7. Zeilinger S, Kuhnel B, Klopp N, Baurecht H, Kleinschmidt A, Gieger C, et al. Tobacco smoking leads to extensive genome-wide changes in DNA methylation. PLoS One 2013; 8(5): e63812. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2461